2018
DOI: 10.4143/crt.2017.351
|View full text |Cite
|
Sign up to set email alerts
|

APEX1 Polymorphism and Mercaptopurine-Related Early Onset Neutropenia in Pediatric Acute Lymphoblastic Leukemia

Abstract: PurposeMercaptopurine (MP) is one of the main chemotherapeutics for acute lymphoblastic leukemia (ALL). To improve treatment outcomes, constant MP dose titration is essential to maintain steady drug exposure, while minimizing myelosuppression. We performed two-stage analyses to identify genetic determinants of MP-related neutropenia in Korean pediatric ALL patients.Materials and MethodsTargeted sequencing of 40 patients who exhibited definite MP intolerance was conducted using a novel panel of 211 pharmacogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…A previous study reported that East Asian genetic ancestry remained associated with 6-MP dose intensity after adjusting for rs116855232 [ 17 ], suggesting that there may be other undiscovered genetic or environmental factors affecting Asians. Kim et al [ 32 ], recently reported that APEX1 rs2307486 variants conferred an increased risk of mercaptopurine-related early onset neutropenia in Korean pediatric ALL patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that East Asian genetic ancestry remained associated with 6-MP dose intensity after adjusting for rs116855232 [ 17 ], suggesting that there may be other undiscovered genetic or environmental factors affecting Asians. Kim et al [ 32 ], recently reported that APEX1 rs2307486 variants conferred an increased risk of mercaptopurine-related early onset neutropenia in Korean pediatric ALL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants in Apurinic/Apyrimidinic Endodeoxyribonuclease 1 (APEX1) have been studied in relation to a more general sensitivity to antimetabolite active drugs, as human APEX1 is involved in DNA base excision repair pathway. In Asian populations APEX1 (rs2307486) variant resulted in an increased risk of 6MP-related early onset neutropenia (Kim et al, 2018).…”
Section: Genetic Variances and Toxicitymentioning
confidence: 99%
“…Transporter genes have also been studied and variants in the ABCB1 gene (C1236T) have found to be associated with increased sensitivity to 6MP (Gervasini et al, 2017), as well as variant genes in efflux transporter ABCC4 (Kim et al, 2018;Tanaka et al, 2018). These findings have been reported in small studies and need confirmation before being introduced in clinical practice.…”
Section: Genetic Variances and Toxicitymentioning
confidence: 99%
“…The recorded 6-MP dose per square meter of the body surface over a 12-week cycle was used to define the actual administered dose as a percentage of the planned dose as the last-cycle DIP. Since East Asian ancestry requires significantly lower 6-MP dose intensity compared to the other ethnic groups [5], patients who require less than 25% of the protocol planned dose were classified as MP-intolerant groups [6]. We have previously presented a detailed description of the subjects and a summary of the measurements [7].…”
Section: Subjectsmentioning
confidence: 99%
“…5 Seoul National University Cancer Research Institute, Seoul, South Korea. 6 Department of Pediatrics, Seoul National University Bundang Hospital, Seoul, South Korea. 7 Department of Pediatrics, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, South Korea.…”
Section: Supplementary Informationmentioning
confidence: 99%